2005
DOI: 10.1002/jmri.20277
|View full text |Cite
|
Sign up to set email alerts
|

Improved artery delineation in dual‐stack coronary magnetic resonance angiography using parallel imaging at 3 T

Abstract: Purpose: To improve vessel sharpness and T2 preparation (T2Prep) in dual-stack three-dimensional coronary magnetic resonance angiography (MRA) by shortening the time delays between the magnetization preparation pulses and the imaging stacks using sensitivity encoding (SENSE) at 3 T. Materials and Methods:By combining dual-stack threedimensional coronary MRA with the parallel imaging technique SENSE at 3 T, the acquisition duration of each threedimensional imaging stack was shortened by a factor of 2. The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This concept has been demonstrated by Huber et al (22) where coronary image quality was preserved despite the two‐fold reduction of scan time achieved by using SENSE at 3T. Utilizing SENSE at 3T has also been shown to be a valuable combination to shorten acquisition widows allowing for simultaneous acquisition of the right and left coronary arteries using two different 3D slabs during diastole without compromising image quality (23).…”
Section: Discussionmentioning
confidence: 98%
“…This concept has been demonstrated by Huber et al (22) where coronary image quality was preserved despite the two‐fold reduction of scan time achieved by using SENSE at 3T. Utilizing SENSE at 3T has also been shown to be a valuable combination to shorten acquisition widows allowing for simultaneous acquisition of the right and left coronary arteries using two different 3D slabs during diastole without compromising image quality (23).…”
Section: Discussionmentioning
confidence: 98%
“…At 3 T, Huber et al (26) demonstrated that 2‐fold SENSE‐accelerated coronary MRA image quality approaches that of more conventional nonaccelerated coronary MRA, while scanning time can be reduced considerably. Another powerful approach includes shortening of the ACQ window using SENSE and thus allowing for simultaneous ACQ of the right and left coronary arterial system (27), thereby increasing volumetric coverage at no extra cost in scanning time.…”
Section: Discussionmentioning
confidence: 96%